Efficacy and Safety of Eravacycline Combination Therapy for Carbapenem-Resistant Acinetobacter baumannii Pneumonia in ICU Patients: A Retrospective Study - Guo Q; Wei Y; Zhao Q; Zhang W; Lv P; Zhou Z; Wang S (Infection and Drug Resistance)
Qingli Guo,1,* Yifei Wei,2,* Qiongrui Zhao,3 Wenping Zhang,4 Pin Lv,5 Zhimin Zhou,1 Shanmei Wang6 1Department of Clinical Laboratory, Xuchang People’s Hospital, Xuchang, Henan, People’s Republic of China; 2Department of Clinical Laboratory, Henan University People’s Hospital, Henan Provincial People’s Hospital, Zhengzhou, Henan, People’s Republic of China; 3Research and Foreign Affairs Office, Henan Provincial People’s Hospital, Zhengzhou, Henan, People’s Republic of China; 4Department of Respiratory and Critical Care Medicine, People’s Hospital of Henan Province, People’s Hospital of Zhengzhou University, People’s Hospital of Henan University, Zhengzhou, Henan, People’s Republic of China; 5Department of Pharmacy Henan Provincial People’s Hospital, Zhengzhou, Henan, People’s Republic of China; 6Department of Clinical Microbiology, Henan Provincial People’s Hospital, Zhengzhou University People’s Hospital, Henan University People’s Hospital, Zhengzhou, Henan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shanmei Wang, Department of Clinical Laboratory, Henan Provincial People’s Hospital, No. 7, Weiwu Road, Zhengzhou, Henan, 450003, People’s Republic of China, Tel +86 137 8353 0126, Email wsm1997@zzu.edu.cnIntroduction: The rising incidence of carbapenem-resistant Acinetobacter baumannii (CRAB) poses challenges in Intensive Care Unit (ICU) settings. Eravacycline, the first fluorocycline antibiotic introduced globally, is increasingly utilized for CRAB-related infections. This study compares eravacycline with tigecycline for CRAB pneumonia in ICU patients.Methods: This retrospective study analyzed 65 ICU patients with CRAB pneumonia treated at Henan Provincial People’s Hospital from September 2023 to March 2024; the clinical efficacy and adverse reactions of eravacycline and tigecycline as target therapies were compared.Results: Both CRAB pneumonia cohorts exhibited more than 50% co-infection rates, predominantly Aspergillus and Klebsiella pneumoniae. Multiple organ dysfunction syndrome (MODS) incidence was significantly higher in the eravacycline group (45.5% vs 15.5%, P< 0.05). Prior to target-drug administration, patients in the eravacycline group showed a longer duration of antibiotic therapy (19.79 ± 9.97 days vs 14.25 ± 7.98 days; P< 0.05). Similarly, the median hospital stay was longer in the eravacycline group [27 (19.50, 39.00) days] versus the tigecycline group [19 (14.00, 29.00) days]. After the index culture, the median time to antibiotic initiation was longer in the eravacycline group than in the tigecycline group (6.52 ± 5.03 days vs 4.09 ± 3.14 days; P < 0.05). The 30-day mortality rate was lower in the eravacycline group than in the tigecycline group (15.2% vs 25.0%). Notably, no deaths occurred among eravacycline-treated patients who received infectious disease specialist consultations. Infection symptom resolution and cure rates did not differ significantly between the two groups.Conclusion: Eravacycline demonstrated non-inferior efficacy to tigecycline in CRAB pneumonia treatment, with a favorable safety profile. Prompt consultation with infectious disease specialists and timely initiation of eravacycline therapy following the index culture are crucial factors in enhancing clinical outcomes.Keywords: CRAB, ICU, pneumonia, eravacycline, tigecycline, clinical efficacy